High Performance Work Systems as an Enabling Structure for Self-organized Learning Processes - Wallner, Thomas; Menrad, Martin (International Journal of Advanced Corporate Learning (iJAC), 2012)
High Performance Work Systems (HPWSs) as a new way of organizing work in general and of production work in particular provide an environment, where self-organized learningprocesses are enabled and fostered. In an extensive research project in 2 major Austrian manufacturing companies we currently investigate the applicability and the effects of HPWS including issues of learning and knowledge management. In this contribution we present the results of the first phase of this project discussing early empirical findings of an exploratory nature.